Mitochondrial fission factor (MFF) frameshift variant in Bullmastiffs with mitochondrial fission encephalopathy. (9th September 2022) - Christen, Matthias; Gutierrez‐Quintana, Rodrigo; Vandenberghe, Helene; Kaczmarska, Adriana; Penderis, Jacques; José‐López, Roberto; Rupp, Angie; Griffiths, Ian R.; Jagannathan, Vidhya; Leeb, Tosso
Abstract: Familial cerebellar ataxia with hydrocephalus in Bullmastiffs was described almost 40 years ago as a monogenic autosomal recessive trait. We investigated two young Bullmastiffs showing similar clinical signs. They developed progressive gait and behavioural abnormalities with an onset at around 6 months of age. Neurological assessment was consistent with a multifocal brain disease. Magnetic resonance imaging of the brain showed intra‐axial bilateral symmetrical focal lesions localised to the cerebellar nuclei. Based on the juvenile age, nature of neurological deficits and imaging findings, an inherited disorder of the brain was suspected. We sequenced the genome of one affected Bullmastiff. The data were compared with 782 control genomes of dogs from diverse breeds. This search revealed a private homozygous frameshift variant in the MFF gene in the affected dog, XM_038574000.1:c.471_475delinsCGCTCT, that is predicted to truncate 55% of the wild type MFF open reading frame, XP_038429928.1: p.(Glu158Alafs*14). Human patients with pathogenic MFF variants suffer from 'encephalopathy due to defective mitochondrial and peroxisomal fission 2'. Archived samples from two additional affected Bullmastiffs related to the originally described cases were obtained. Genotypes in a cohort of four affected and 70 unaffected Bullmastiffs showed perfect segregation with the disease phenotype. The available data together with information from previous disease reports allow classification of the investigated MFF frameshift variant as pathogenic and probably causative defect of the observed neurological phenotype. In analogy to the human phenotype, we propose to rename this disease 'mitochondrial fission encephalopathy (MFE)'.